The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1111/j.1365-2559.2012.04288.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparing virtual with conventional microscopy for the consensus diagnosis of Barrett’s neoplasia in the AspECT Barrett’s chemoprevention trial pathology audit

Abstract: Diagnostic agreement with virtual microscopy compares favourably with conventional microscopy in what is recognized to be a challenging area of diagnostic practice. However, this study highlights possible limitations for this method in the primary diagnostic setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…Diagnostic accuracy of VM for GI tract neoplasia was compared with that for CLM in a U.K. study (comparative analysis, n = 61). 106 Here again, ''.there was substantial reliability of diagnostic agreement (j = 0.712) scoring the 61 biopsies and moderate agreement scoring the subgroup of 33 positive biopsies with both conventional microscopy (j = 0.598) and virtual microscopy (j = 0.436). Interobserver diagnostic agreement between two pathologists by virtual microscopy was substantial (j = 0.76).…”
Section: Telepathology Evidence: Feasibility and Acceptancementioning
confidence: 90%
“…Diagnostic accuracy of VM for GI tract neoplasia was compared with that for CLM in a U.K. study (comparative analysis, n = 61). 106 Here again, ''.there was substantial reliability of diagnostic agreement (j = 0.712) scoring the 61 biopsies and moderate agreement scoring the subgroup of 33 positive biopsies with both conventional microscopy (j = 0.598) and virtual microscopy (j = 0.436). Interobserver diagnostic agreement between two pathologists by virtual microscopy was substantial (j = 0.76).…”
Section: Telepathology Evidence: Feasibility and Acceptancementioning
confidence: 90%
“…* The PCR for studies on the gastrointestinal system ranged from 70.0% to 99%. 29,31,43,53,55,57,59 Table 3 displays the PCRs for each organ system included.…”
Section: Diagnostic Concordancementioning
confidence: 99%
“…10 Several studies in recent years have demonstrated that primary histopathologic diagnoses can be rendered digitally using WSI. [11][12][13][14][15][16][17][18] Discrepancies in diagnoses between digital and glass slides in publications were attributed to image quality, rarely missed tissue on the digital image, inadequate clinical metadata, and pathologists' lack of experience using the WSI system. Specific microscopic details (eg, organisms, nuclear atypia, apoptosis, mitotic figures, eosinophil granules) were sometimes noted to be difficult to identify because of poor image resolution on high magnification or went undetected (eg, minute focus of prostate adenocarcinoma) in the digital image.…”
mentioning
confidence: 99%